Respostas

  • Usuário do Brainly
2014-05-20T21:39:31-03:00
4x² - 100 = 0
4x² = 100
x² = 100/4
x² = 25
x = ± √25
x = ± 5

3x² + 48 = 0
3x² = - 48
x² = - 48/3
x² = - 16
x = ± √- 16
x = ± (- 4)
x = ± 4

- 2x² + 64 = 0
- 2x² = - 64 . (- 1)
2x² = 64
x² = 64/2
x² = 32
x = ± √32
x = ± √2^5
x = ± √2² . 2² . 2
x = ± 2 . 2√2
x = ± 4√2

x . (x - 2) = 1 - 2x
x² - 2x = 1 - 2x
x² - 2x + 2x - 1 = 0
x² - 1 = 0
x² = 1
x = ± √1
x = ± 1

3x²/4 = x² + 7/6
18x² = 4x² + 28
18x² - 4x² = 28
14x² = 28
x² = 28/14
x² = 2
x = ± √2

2x² - 2450 = 0
2x² = 2450
x² = 2450/2
x² = 1225
x = ± √1225
x = ± 35
2 5 2